Pelatihan dan Pendampingan Pembuatan Gula Semut di Desa Patoman Kabupaten Banyuwangi - Pardi, I Wayan; Yudiana, I Kadek; Miskawi, Miskawi (Universitas Muhammadiyah Surabaya, 2019)
The purpose of this service is to train the community in producing and packaging sugar ants made from coconut sap. The service location is in Patoman Tengah Hamlet, Patoman Village, Blimbingsari District, Banyuwangi Regency. Meanwhile, the partners that were made the object of service were unproductive groups of people in producing brown sugar and people who had previously produced printed red sugar but had now stopped because of various kinds of problems. The method used in this training is to bring in experts from the Desperindag Banyuwangi who master the field of making ant sugar. The sugar production process of ants in Patoman Village starts from filtering coconut sap using a filter cloth to remove impurities, the clean coconut juice is then put into a pan and then cooked with a stove. After the head juice becomes thick, it is continued by solidification (compaction). Solid coconut sap continues to stir until it becomes a crystal (crystallization). After the crystal is formed, refinement is also carried out by using wood made of pressure. After that filtering is done using a sieve that has been prepared. The ant sugar is then dried under the sun for 3-4 hours. Finally, the packaging of ant sugar is done using plastic and plastic bottles.Â